The Effect of Advertising and Brand Image on Consumer Purchase Interest of Harum Pucuk Tea at PT Mayora Indah Tbk - Suryanto Sosrowidigdo (Enrichment : Journal of Management, 2021)
In today's business competition, marketing strategy for brand image is very important in a product, because it is possible that existing consumers will not switch to other products because they believe and are loyal to the brand that has been consumed. The method used in this research is descriptive quantitative method, which is a type of research that produces new data obtained by using statistical or measurement procedures. Data collection methods used are observation, questionnaires and documentation. The results of the correlation test prove that there is a very strong influence between advertising, brand image on consumer buying interest with a correlation value of 0.801 which means the correlation between variables is very strong. The results of the coefficient of determination test show that R square is 0.683. The results of the multiple linear regression coefficient test show that Y = 1.239 + 0.310X1 + 0.893X2. The results of the above analysis indicate that PT Mayora Indah Tbk has a very strong and significant influence between advertising and brand image on consumer buying interest and based on the results of the regression equation test, advertising and brand image have a positive effect on consumer purchases. interest